Prioritising the needs of high speed internet subscribers using importance performance analysis: the case of Asia-Tech Company in Shiraz. (2018) - Shahin, Arash; Zolfaghari, Samira
The aim of this study is to prioritise customer requirements in the field of high speed internet. For this purpose, importance performance analysis (IPA) has been used and 13 variables have been investigated. Then, importance and performance questionnaires have been distributed to the customers of Asia-Tech Company in Shiraz and data of 299 returned questionnaires has been analysed. Findings indicate that the three variables of 'initial setup process', 'information about internet' and 'easy connection' are the three top priorities with highest scores of 0.106, 0.892 and 0.083, respectively.